2019
DOI: 10.1111/1475-6773.13134
|View full text |Cite
|
Sign up to set email alerts
|

Medicare expenditures attributable to dementia

Abstract: Objective To estimate dementia's incremental cost to the traditional Medicare program. Data Sources Health and Retirement Study (HRS) survey‐linked Medicare part A and B claims from 1991 to 2012. Study Design We compared Medicare expenditures for 60 months following a claims‐based dementia diagnosis to those for a randomly selected, matched comparison group. Data Collection/Extraction Methods We used a cost estimator that accounts for differential survival between individuals with and without dementia and deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 30 publications
6
78
2
Order By: Relevance
“…Another group of researchers found that community‐dwelling individuals age 65 and older with Alzheimer's dementia had $1,101 (in 2012 dollars; $1,316 in 2019 dollars) higher annual out‐of‐pocket health care spending than individuals without Alzheimer's dementia, after controlling for differences in patient characteristics, with the largest portion of the difference being due to higher spending on home health care and prescription drugs 526 . Furthermore, individuals with Alzheimer's dementia spend 12% of their income on out‐of‐pocket health care services compared with 7% for individuals without Alzheimer's dementia 527 . Another research team found that the five‐year incremental cost of dementia was $15,704 (in 2017 dollars; $16,389 in 2019 dollars), with the additional costs of care in the first year after diagnosis representing 46% of the five‐year incremental costs 527 …”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
See 4 more Smart Citations
“…Another group of researchers found that community‐dwelling individuals age 65 and older with Alzheimer's dementia had $1,101 (in 2012 dollars; $1,316 in 2019 dollars) higher annual out‐of‐pocket health care spending than individuals without Alzheimer's dementia, after controlling for differences in patient characteristics, with the largest portion of the difference being due to higher spending on home health care and prescription drugs 526 . Furthermore, individuals with Alzheimer's dementia spend 12% of their income on out‐of‐pocket health care services compared with 7% for individuals without Alzheimer's dementia 527 . Another research team found that the five‐year incremental cost of dementia was $15,704 (in 2017 dollars; $16,389 in 2019 dollars), with the additional costs of care in the first year after diagnosis representing 46% of the five‐year incremental costs 527 …”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
“…Furthermore, individuals with Alzheimer's dementia spend 12% of their income on out‐of‐pocket health care services compared with 7% for individuals without Alzheimer's dementia 527 . Another research team found that the five‐year incremental cost of dementia was $15,704 (in 2017 dollars; $16,389 in 2019 dollars), with the additional costs of care in the first year after diagnosis representing 46% of the five‐year incremental costs 527 …”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
See 3 more Smart Citations